Identifikasi Sistem Penyediaan Air Minum Di Kecamatan Langgam - Handayani, Devi Tri; Asmura, Jecky; Sasmita, Aryo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Drinking water is water that has gone through a processing process or without any processing that meets the requirements and can be directly drunk. The fulfillment of drinking water needs in Langgam Subdistrict, Pelalawan Regency comes from bottled water, drilled wells, tap water, river water, springs and rainwater, of which the quality and quantity of these sources are not guaranteed. The need for drinking water in Langgam District is calculated based on population projections for the next 20 years with raw water coming from the river using three methods and the Least Square Method chosen. From the calculation of the prediction, the population in Langgam District in 2038 will reach 65,719 people, where in the planning, all residents will be served drinking water with a house connection type. The total average water requirement in Langgam District is 180.31 L / second, the maximum water requirement is 138.6 L / second and the peak hour water requirement is 188.9 L / second. Keywords: Langgam, Water Needs, River